2007
DOI: 10.1063/1.2644614
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Binary Ag-Cu Ion Mixtures in Zeolites: Their Reduction Products and Stability to Air Oxidation

Abstract: A series of Ag +-Cu 2+ binary mixtures with different Ag/Cu ratios were supported on mordenite with different Si/Al ratios and were subsequently reduced under hydrogen in the temperature range 323K-473K. Ag and Cu K-edge X-ray Absorption Spectroscopy (XAS) was conducted on these systems in-situ to monitor the reduction species formed and the kinetics of their reduction. In-situ XANES clearly demonstrates that the formation of silver particles is severely impeded by the addition of copper and that the copper is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In search of the best method, various stabilizers have been used, such as inorganic salts, organic compounds, organic solvents, biological molecules, etc. The influence of the composition of zeolites, that is, their Si/Al ratio, as well as the influence of other exchangeable counter-cations in a binary or ternary mixture of metal cations over zeolite systems have been widely investigated [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In search of the best method, various stabilizers have been used, such as inorganic salts, organic compounds, organic solvents, biological molecules, etc. The influence of the composition of zeolites, that is, their Si/Al ratio, as well as the influence of other exchangeable counter-cations in a binary or ternary mixture of metal cations over zeolite systems have been widely investigated [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations for the use of these materials is the low stability of certain types of copper species [24,44], mainly at low levels of aggregation (nm) and certain states of oxidation (0 and 1+). We paid special attention to the study of copper species deposited on natural and synthetic zeolites in multimetallic systems [4,26,[29][30][31][32]. It has been shown that the addition of a second metal (for example, Zn and Ag) can significantly affect the stabilization of a certain type of copper species and the degree of aggregation of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%